IMPLEMENTASI PROGRAM UBUDIYAH SEBAGAI UPAYA PEMBENTUKAN KARAKTER SISWA DI SMA ISLAM AL MAARIF SINGOSARI - Siti Khoiriyah; Rosichin Mansur; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Al Maarif Singosari Islamic High School, helps and builds character through the Ubudiyah Program which is currently very much needed according to researchers. In this study, this type of research approach uses a case study. Data collection techniques using observation, interviews and documentation. The data source uses primary data sources. The data analysis technique was carried out in three stages, namely data reduction, data presentation and data verification. From the research that has been done, it can be concluded that, 1). The planning of the Ubudiyah program is designed by the curriculum and carried out by honorary teachers and several teachers who are entrusted with helping the program. 2) Implementation of the ubudiyah program as an effort to build the character of students at Al Maarif Singosari Islamic High School, namely through religious activities such as dhuhur prayers in congregation, guidance on reading the Qur'an and SKU (Ubudiyah Proficiency Standards). 3) The results of the implementation of the ubudiyah program are students at Al Maarif Singosari Islamic High School, namely students are more polite, towards parents, teachers, friends. Students continue the habit of praying in congregation, Students are more honest in learning including attendance and student assignments independently.